The performance of physical activity and health-related quality of life in patients with heart failure: a cross-sectional study - Ruku, Denny Maurits; Chen, Hsing Mei (Universitas Airlangga, 2024)
Introduction: This study aimed to describe self-reported PA performance and determine predictors regarding health-related quality of life (HRQOL) among heart failure (HF) patients. Methods: A cross-sectional design was adopted, and data were collected using a questionnaire comprising demographic characteristics, illness-related factors, self-report health status (SRHS) questionnaire, international PA questionnaire, and Minnesota Living with Heart Failure questionnaire. Subsequently, data were analyzed using Pearson correlation coefficient, t-test, one-way ANOVA, and hierarchical multiple regression. Results: The mean age for the total participants of 180 HF patients was 59.92 ± 11.90 years, with 60% being male, and the mean HRQOL score was 42.96 ± 20.47. HRQOL had significant correlations with HF medication (r= 0.20, p< 0.01), health status (HS) (r= 0.35, p< 0.01), PA (r= -0.52, p< 0.01), and HRQOL was associated with the New York Heart Association (NYHA) classification (F= 94.57, p< 0.001). Meanwhile, age, gender, job, marital status, religion, level of education, hemoglobin, body mass index, length of diagnostic HF, and comorbidities did not have a significant relationship with HRQOL. Three variables were significant predictors of HRQOL, namely HS (β= 0.21, p< 0.01), NYHA Class III (β= 0.15, p< 0.05), and PA (β= -0.31, p< 0.001). Conclusions: Regular PA is crucial in improving HRQOL of HF patients. In addition, HS, HF medication, and NYHA Class should be considered in providing care for HF patients aimed at improving HRQOL.